The Competencies of Daycare Caregivers in Building Interaction and Attachment with Children to Optimize Their Cognitive Development - Selinna Sandrinia Zainuddin; Ni Made Surianti; Alfiasari (Journal of Family Sciences, 2021)
Families whose parents are both working have limited time in nurturing their children. This circumstance makes parents, especially mothers, alternate parenting to the babysitter or caring institution called daycare. This study aimed to analyze the correlation of children's characteristics, caregiver-child interaction, and attachment with the cognitive development of preschool children in daycare. This study used a cross-sectional study design with the daycare (TPA) selection as the research location carried out purposively located in the buffer areas of the capital city of DKI Jakarta. Respondents in this study were 39 children aged 2.5-6.4 years with complete parents and 16 caregivers from four selected TPA who interacted with their children daily. Data was collected by means of in-depth observations to measure the interaction variables between caregivers and children. This study indicates a positive correlation between caregiver-child interaction and attachment with a child's cognitive development. This study also found a signiﬁcant positive relationship between the caregivers-child interaction with caregivers-child attachments and a significant negative relationship between the child's age and the caregivers-child attachment. This shows that interaction, and attachment between caregivers and children are important factors that can improve cognitive development while in TPA.